The Concern for People’s Livelihood in State Governance in the Early Ming Dynasty - Fang Zhiyuan (Frontiers of history in China, 2023)
Attaching importance to people’s livelihood is not only an important measure for rulers to consolidate their power, but also a concrete expression of Confucianism’s people-oriented thinking in state governance. Based on his own experience and his understanding of social relations in the late Yuan and early Ming dynasties, Zhu Yuanzhang, the founder of the Ming Dynasty, regarded the people at the bottom as the “foundation of the state,” and his concern for people’s livelihood became an important part of his governance. The development of China’s unified multi-ethnic state, including the Ming Dynasty, has repeatedly shown one fact: between success and failure, there are only two words—people’s livelihood.